Genetic Variation on Body Weight and Daily Body Weight Gain of Boer Crosses and Khari Goats Kids at Mid-Hills of Nepal (Journal of the Bangladesh Agricultural University, 2025)
Research was done at the National Goat Research Program, NARC, Bandipur, Tanahun, Nepal with the objective to identify the pattern of live weight changes (kg) and daily weight gain (g/day) of different genetic groups of Boer crosses (Boer 75% and Boer 50% genotypes) and Khari goats from birth to yearling. The live weight of goats at different stages of growth were taken and recorded properly. Five hundred sixty-nine kids for birth weight, 534 kids for weaning weight (3 months), 467 for six-month weight, 320 for nine-month weight, and 279 for twelve-month weight were used in this study. Findings revealed that the body weight of different genetic groups (Boer 75%, Boer 50% and Khari) at birth to nine months, except 3 months was statistically similar (p>0.05) for Boer 50% and Boer 75% blood level, but Boer 75% blood level was significantly (p